HICOM Automotive celebrates 1st batch of graduates - UMP, PNC (Penerbit UMP, 2010)
HICOM Automotive Manufacturer (M) Sdn Bhd in Pekan, Pahang, celebrated its first batch of graduates when 24 of its staff completed their studies in Industry Technology Management's (ITM) Executive Diploma Programme recently.